Continuance participation model for online communities - Shanmugam, Mohana (2017)
The models that predict constructs of individuals’ acceptance are predominantly based on pre-adoption intention and behaviour rather than post-adoption. Although within the field of Information Systems (IS) a number of continuance models have been developed and tested for efficacy the capabilities of these models are limited because its underlying conceptualization of predicting acceptance behaviour underestimated social related influences. The lack of social related influences in continuance participation models affects the sustainability of online communities. Moreover, many online communities that spring up fail due to the limitation and lack of attention given for social needs of individuals. To overcome the mentioned limitations, a Continuance Participation Model (CPM) for online communities is presented and evaluated. The model attempted to define the relationship between the Theories of Planned Behaviour (TPB) and Social Support (SST) alongside satisfaction and perceived value constructs towards the continuance participation intention and behaviour of online communities. The constructs contributing to the model is identified based on extensive literature review and Average Congruency Percentage (ACP) verified and validated by three panels of experts. This study is established on a positivist approach in which a quantitative methodology is used to investigate the correlational paths. Using a probability sampling method, data was collected from 385 users of social networking sites (SNSs) with a minimum of two years of experience. Hypothetical relationships were examined using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS). The study findings indicate that the CPM achieved an acceptable fit with the data and specifically 9 out of 10 hypotheses were met. The empirical evidence also reveals that social support constructs measured by informational and emotional support exert significant effects on the intention and behaviour as well as exerts positive effects on perceived value and the intention to continue participating in online communities. Subsequently, this research introduces an Implementation framework (IF) to evaluate the sustainability of online communities. The appropriateness and importance of the components in the IF are validated by four experts from the academia and industry. Based on these findings, a prototype called Online Communities Checklist Tool (OC2T) is developed and evaluated. A user acceptance test using the Perceived Usefulness and Ease of Use (PUEU) instrument conducted with fifteen developers’ demonstrated overall feasibility and acceptability of the prototype. Results further reveal that the OC2T is beneficial in evaluating the sustainability of online communities. Finally, this study develops research in online communities by proposing social constructs from a social psychology theory in increasing our understanding on continuance participation models in online communities.